Self-organized TiO2 nanotubes grown on Ti substrates with different crystallographic preferential orientations: Local structure of TiO2 nanotubes vs. photo-electrochemical response - Krbal, Milos; Sopha, Hanna; Pohl, Darius; Beneš, Ludvík; Damm, Christine; Rellinghaus, Bernd; Bezdička, Petr; Šubrt, Jan; Macák, Jan (Elsevier, 2018)
Here we report on structural properties and the photo-electrochemical response of annealed TiO2 nanotube layers, grown on four different Ti substrates by an identical anodization process. TiO2 nanotube layers were grown on Ti substrates by anodization in glycerol containing NH4F and water. The layers were then annealed at 400 °C for 1 hour in air. Photocurrent densities of annealed nanotubes were recorded upon irradiation with ultraviolet (UV) light at a constant potential of 0.4 V, in a 0.1 M Na2SO4 aqueous solution. Approximately, a 280 % difference in the photocurrent densities was recorded from TiO2 nanotubes fabricated from different Ti substrates. To elucidate the origin of this difference, the nanotube layers were scrutinized by Mott-Schottky measurements, X-ray diffraction (XRD) and Electron Energy Loss Spectroscopy (EELS). Inspection of the XRD patterns revealed preferential crystallographic orientations in various Ti substrates from which TiO2 nanotube layers were produced. Subsequent EELS analyses of the annealed nanotube layers disclosed significant differences in the Ti:O stoichiometry, in accordance with XRD evaluation of preferential orientation differences among used Ti substrates.
Keywords: TiO2 nanotubes; Anodization; Anatase; Photo-current; Stoichiometry